If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = 5x + 4x + 3 Reorder the terms: 3 = 3 + 5x + 4x Combine like terms: 5x + 4x = 9x 3 = 3 + 9x Add '-3' to each side of the equation. 3 + -3 = 3 + -3 + 9x Combine like terms: 3 + -3 = 0 0 = 3 + -3 + 9x Combine like terms: 3 + -3 = 0 0 = 0 + 9x 0 = 9x Solving 0 = 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 0 + -9x = 9x + -9x Remove the zero: -9x = 9x + -9x Combine like terms: 9x + -9x = 0 -9x = 0 Divide each side by '-9'. x = 0 Simplifying x = 0
| 7z^2-12z+20= | | -3(5w+v)-2(-3v+3w)= | | -5.6*-14.3= | | 342=23*b | | xy-xz=b-c | | -5.6x-14.3= | | -9x+13=-27 | | x-8=4-2(3x+5) | | 3d+8=6d-2 | | n+1=-17-10n-2+9n | | xy-zy=b-c | | -n-24=5-q | | 8x+38=3(x+1) | | xy-zy=b | | 2t^3-10t=t^2 | | 15-3x=15-3x | | 7x-6-4x=2x+6 | | 10-15x=35 | | 46-7x=12+10x | | 0.3333333333333333= | | 3xy+yx= | | 3x-4=6x-1 | | ax+bc+3=-6 | | -129=6(1-4n)-3n | | -(5w+u)+3(3u+5w)= | | 4z-5=19 | | 4x=4x+7 | | -4+5k=11 | | 3x^3+5x-8=0 | | (6-5s)(2-s)= | | 7+10r=77 | | 24+13=24+15 |